How to Appropriate Sustainable Development Goals in Madagascar’s Context - Rakotoarivelo M. M; Ravalison J.; Razafindrazanakolona A. D.; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B. (Britain International of Exact Sciences (BIoEx) Journal, 2023)
Despite its socio-economic vulnerability, Madagascar has committed itself to carrying out development actions that are reflected in its National Policy. The aim of this study is to produce recommendations for decision-makers on local realities that need to be taken into account regarding the implementation of Sustainable Development Goals. To proceed, four Sustainable Development Goals or SDGs that directly concern cities have been chosen such as: SDG 6 “clean water and sanitation”, SDG 7 “clean and affordable energy”, SDG 11 “sustainable cities and communities” and SDG 12 “responsible consumption and production”. The main methodology is based on an inductive method with a multiscalar approach that starts from the study of the particular case of Ambositra, the locality chosen for this study, to express an opinion on a broader and generalized perspective of Malagasy cities' situations. These results are highlighted: low access to clean water and sanitation, outdated and inadequate public infrastructure and facilities; polluting and non-renewable energy consumption. However, opportunities exist and can be used to achieve these four objectives. Sustainable development is a long-term task which must be included into local development frameworks.